PREVALENCE OF GASTROINTESTINAL PARASITES OF CATTLE AND SHEEP IN ANIMAL PRODUCTION RESEARCH FARM, FEDERAL UNIVERSITY OF TECHNOLOGY, MINNA, NIGER STATE, NORTH CENTRAL, NIGERIA - Adamu, Amina Yawo; Wani, Chubiyojo Victoria; Adamu, Fatima Ndagi; Faisal, Abubakar; Abduganiyu, Khadija; Lawal, Saudat; Adamu, Fadila (FUDMA Journal of Sciences, 2026)
A cross sectional study was carried out to determine the prevalence of Gastrointestinal Parasites of Cattle and Sheep in animal production research farm, Federal University of Technology Minna,  using centrifugal floatation and sedimentation technique. A total of one hundred and fifty (150) faecal samples were collected from cattle (75) and Sheep (75). An overall prevalence of 52.7% was recorded. Cattle (56%) had the highest prevalence than Sheep (49.3%) and the difference was non-significant (P>0.05). Seven (7) gastrointestinal parasites were encountered namely: Toxocara spp (12%), Strongyloides spp (4%), Strongyle spp (14.7%), Eimeria spp (10.7%), Taenia spp (5.3%), Monieza spp (3.3%) and Fasciola spp (2.7%). Strongyle spp (14.7%) had the highest prevalence while the least prevalence was Fasciola spp (2.7%). Male cattle (62.9%), male sheep (64%), adult cattle (60%), young sheep (58.6%) and pregnant cattle (70%) were more infected than female cattle (50%), female sheep (42%), young cattle (50%), adult sheep (43.5%) and non-pregnant cattle (33.3%) and the difference was not significant (P>0.0). Pregnant sheep (66.7%) were more infected than non-pregnant sheep (20%) and a significant difference was observed (P
Keywords: Gastrointestinal; Parasites; Cattle; Sheep; Research; Prevalence